2021
DOI: 10.1016/j.jaridenv.2021.104445
|View full text |Cite
|
Sign up to set email alerts
|

How far surface water fluxes determine restoration success in Mediterranean degraded areas? Implications for dryland precision restoration

Abstract: Drylands functioning depends on water fluxes and the retention of resources. The restoration of degraded areas should mimic the natural arrangement of vegetation in the landscape in a source-sink pattern.Reintroducing key woody seedlings through planting is a major concern in ecological restoration as these areas use to be overpassed degradation thresholds and ecosystem functions are limited. However, it is not clear how natural fluxes might determine seedlings performance of key shrub species. We have analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(42 reference statements)
0
1
0
2
Order By: Relevance
“…(5) Low-cost actions with many associated benefits: it has been widely reported that resources management may improve ecosystem functioning and the provision of services, while minimizing costs [30,77]. The use of innovative low-cost techniques appears to be a good option to optimize resource availability rather than other more expensive options like irrigation systems [78]. Microcatchments have been previously tested with positive (4) Accurate species selection, seed provenance and suitable plant nursery techniques: determining proper ecosystem references allows detailed species selection to be carried that suits the specific physiographic characteristics of the restoring area.…”
Section: Results Analysis and Lessons Learnedmentioning
confidence: 99%
“…(5) Low-cost actions with many associated benefits: it has been widely reported that resources management may improve ecosystem functioning and the provision of services, while minimizing costs [30,77]. The use of innovative low-cost techniques appears to be a good option to optimize resource availability rather than other more expensive options like irrigation systems [78]. Microcatchments have been previously tested with positive (4) Accurate species selection, seed provenance and suitable plant nursery techniques: determining proper ecosystem references allows detailed species selection to be carried that suits the specific physiographic characteristics of the restoring area.…”
Section: Results Analysis and Lessons Learnedmentioning
confidence: 99%
“…Usando un modelo espacialmente explícito, Berghuis et al (2020) encontraron también una relación unimodal entre el tamaño de sumideros artificiales distribuidos de forma regular sobre una ladera de suelo desnudo y la biomasa vegetal promovida por esta acción. El crecimiento y el estado general de las plantas en una mancha de vegetación dependen positivamente del tamaño de su área fuente (Urgeghe y Bautista 2015), pero esta relación tiende a un valor máximo cuando se satura la capacidad sumidero de la mancha (Smanis et al 2021), abundando en la idea de una proporción óptima de fuentes y sumideros (Puigdefábregas et al 1999). Algunos trabajos con modelos muestran, sin embargo, que coberturas iniciales de sumideros muy bajas puede ser suficiente para desencadenar el restablecimiento de una cubierta vegetal discontinua en el ecosistema (Mayor et al 2019;Berghuis et al 2020).…”
Section: Gestión De La Conectividad Para Controlar La Degradación Y F...unclassified
“…Several management decisions can increase mortality in dryland plantations regardless of meteorology, such as shallow site preparation (Palacios et al, 2009, Löf et al, 2012Smanis et al, 2021), unsuitable planting timing (McTague and Tinus, 1996;Pardos et al, 2003), pre-planting mishandling of plant stock (Edgren, 1984), careless execution of planting (Mullin, 1974;Long, 1991) or inadequate species selection (Suárez et al, 2011;Meli et al, 2014;del Campo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%